Pengaruh Penerapan Media Animasi Audio Visual Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS Kelas IV Di SDN 04 Pedamaran Oki Sumatera Selatan - Resi Relista; Djoko Rohadi Wibowo (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to determine student learning outcomes before and after applying audio-visual animation media to social studies subjects for grade IV SDN 04 Pedamaran, and to the effect of applying audio-visual animation media to student learning outcomes in grade IV at SDN 04 Pedamaran. Subjects in this study amounted to 22 students. This study uses a descriptive quantitative method with data collection techniques in the form of; observation, interviews, tests, and documentation. The analysis in this study uses the statistical formula for the "t" test for two small samples (N less than 30), while the two small samples have a relationship with each other. The results of this study are: 1) The average score of students before applying audio-visual animation media in class IVb is 62.28. 2) The average value after applying audio-visual animation media is 82.72. The test scores of student learning outcomes after the application of audio-visual animation media (post-test) increased or were better than student learning outcomes before the application of audio-visual animation media in the initial test (pre-test) in social studies subjects for class IV SDN 04 Pedamaran. 3) By comparing the amount of "t" obtained in the calculation (= 9.217) and the amount of "t" listed in the table of t values ​​(5% = 2.831 and 1% = 2.517) it is known that is greater than 2.831 < 9.217 > 2.517. The value is greater than because of the difference in student learning outcomes test scores between before and after applying audio-visual animation media to social studies subjects on types of work, which is a significant difference or a convincing (significant). So that can be concluded that audio-visual animation media has a significant influence on student learning outcomes in social studies subjects, material types of work in class IV at SDN 04 Pedamaran.